TNF superfamily cytokines and receptors in the healthy and diseased immune system - Siegel, Richard (Henry Stewart Talks, 2011)
Genomics of the TNF/TNFR superfamily, TNF/TNFR signaling types, Various domains of TNFR, TNF ligands and receptor binding, Fas and the TNFR family, Apoptosis through DISC recruitment, FAS-FADD crystal structure, Gene expression through TRAF proteins and regulation by dynamic expression of ligands, Lymph node development, Innate immunity enhancement, B & T cells and the TNFR superfamily, Multiple programmed cell death pathways, Osteoclast development, Molecular mechanisms of genetic diseases and defects in the Fas pathway, Fas intra and extracellular mutations, Therapeutics and anti-inflammatory uses of TNF superfamily blockade